(3OQGSI fXQjI JWHjbjI dBdjI GdEfaGPs - (3Wg CMeO Ydj(B, (3bGSes ((3GdEScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI ddfTQ(B,s, 2012)
(3GdCSGS GdbGfhfj ddEeJKGd(B- (3GdWHjYI GdbGfhfjI ddJOGHjQ GdeVGOI aj EWGQ GdfXGe GdbGfhfj defXeI GdJLGQI GdYGdejI(B- (3GdeHGOF GdYGeI GdMGceI ddJOGHjQ GdeVGOI aj efXeI GdJLGQI GdYGdejI(B- (3GdTQhW GdbGfhfjI GdhGLHI ddJQNjU HEJNGP GdJOGHjQ GdeVGOI aj efXeI GdJLGQI GdYGdejI (B- (3JWHjb GdJOGHjQ GdeVGOI aj EWGQ JShjI efGRYGJ GdJLGQI GdOhdjI(B- (3GdJMOjGJ hGdMdhd GdebJQMIs
Keywords: (3GdJLGQI GdYGdejIs; (3GdJMcjes; (3GdJMcje GdOhdjs; (3efXeI GdJLGQI GdYGdejIs